Comparison of arch form between ethnic Malays and Malaysian aborigines in peninsular Malaysia - Othman, S.A.; Xinwei, E.S.; Lim, Sheh Yinn; Jamaludin, Marhazlinda; Mohamed, Nor Himazian; Yusof, Z.Y.M.; Shoaib, Lily Azura; Hussein, Nik Noriah Nik (2012)
Objective: To determine and compare the frequency distribution of various arch shapes in ethnic Malays and Malaysian Aborigines in Peninsular Malaysia and to investigate the morphological diff erences of arch form between these two ethnic groups. Methods: We examined 120 ethnic Malay study models (60 maxillary, 60 mandibular) and 129 Malaysian Aboriginal study models (66 maxillary, 63 mandibular). We marked 18 buccal tips and incisor line angles on each model, and digitized them using 2-dimensional coordinate system. Dental arches were classified as square, ovoid, or tapered by printing the scanned images and superimposing Orthoform arch templates on them. Results: Th e most common maxillary arch shape in both ethnic groups was ovoid, as was the most common mandibular arch shape among ethnic Malay females. The rarest arch shape was square. Chi-square tests, indicated that only the distribution of the mandibular arch shape was signifi cantly diff erent between groups (p = 0.040). However, when compared using independent t-tests, there was no difference in the mean value of arch width between groups. Arch shape distribution was not diff erent between genders of either ethnic group, except for the mandibular arch of ethnic Malays. Conclusions: Ethnic Malays and Malaysian Aborigines have similar dental arch dimensions and shapes.